APLIKASI PEMESANAN SPERPART MOTOR PADA TOKO BERODAJAYA BERBASIS ANDROID - Susilowati, Tri; Faturrohman, Andi Halim (JMBI (Journal of Marketing and Business Intelligence), 2024)
The workshop is a small and medium-sized entrepreneur type business that is engaged in repair services, be it motorbikes or cars, more than that, the workshop also conducts business selling spare parts to complete the need for replacement of damaged vehicle spare parts. With the use of this information system, it will make it easier for employees to collect transaction data in the Wheeled Jaya workshop so that it is expected to be able to provide faster, better service and make it easier for workshop owners to manage motorcycle spare data. How to make an Android-based Online Motorcycle Parts Ordering Application Design, in designing this formation system, the author uses the Waterfall Model, there are 5 steps in waterfall mode, the Waterfall Methodology is one of the models in software design. The design of an Android-Based Motorcycle Parts Ordering Application was built using the Embarcadero Delphi 10.4 software and using the java script programming language. Based on testing the Android-Based Motorcycle Parts Ordering Application Design, it can be concluded that the Android-Based Motorcycle Parts Ordering Application System increases consumers to search for motorcycle parts sales shops in Beroda Jaya.